Kebebasan Sejati sebagai Dasar Kekudusan: Refleksi Soal Kebebasan dalam Rangka 30 Tahun Penerbitan Ensiklik Veritatis Splendor - Prastiyo, Ferdian Dwi (Lux et Sal, 2023)
True freedom is an important foundation for the Church's call to holiness. True freedom is the fruit of a person's lived experience of knowing God as the highest truth and desiring God as the highest good. Veritatis Splendor, an encyclical by Pope John Paul II on truth and freedom, emphasizes that human freedom does not have an end in itself but is always dependent on divine truth. This is shown in the attitude of obedience to the law of God, which is a manifestation of God's love and wisdom. Conscience plays an important role in human obedience to God because it is there that a person meets God personally. True freedom is then revealed in moral actions in everyday life where each person is called to imitate the act of martyrdom as moral perfection. The encyclical itself states that martyrdomis a prominent example of the Church's holiness.